2018
DOI: 10.1093/rheumatology/key365
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid score is a novel risk factor for idiopathic osteonecrosis of the femoral head in patients with systemic lupus erythematosus

Abstract: Objective Idiopathic osteonecrosis of the femoral head (ION) is a common complication of SLE associated with CS therapy. Although the pathogenesis of ION involves local bone ischaemia favoured by thrombophilia, the involvement of aPL in lupus ION remains to be elucidated. We have previously reported the aPL score (aPL-S) as a quantitative marker of aPL and the development of thrombotic events in autoimmune diseases. The aim of this study was to identify the impact of aPL on the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 12 publications
1
23
0
1
Order By: Relevance
“…that usage of 0.8 mg/(kg/day) of prednisone was associated with ON. 21 Other studies have shown that a daily dose of 20–39 mg for >1 month increased the risk of ON, 5,12,22 as well as >40 mg for 1 month. 23 Some studies emphasized that the cumulative dose of GC in the first month or first 4 months at SLE onset could be used as a predictor to evaluate the occurrence of ON.…”
Section: Discussionmentioning
confidence: 98%
“…that usage of 0.8 mg/(kg/day) of prednisone was associated with ON. 21 Other studies have shown that a daily dose of 20–39 mg for >1 month increased the risk of ON, 5,12,22 as well as >40 mg for 1 month. 23 Some studies emphasized that the cumulative dose of GC in the first month or first 4 months at SLE onset could be used as a predictor to evaluate the occurrence of ON.…”
Section: Discussionmentioning
confidence: 98%
“…All of them were also receiving therapy for osteoporosis. High-dose corticosteroid may decrease bone formation rapidly and permanently, and increase bone resorption rapidly and temporarily [24]. Indeed, corticosteroid induced osteoblast and osteocyte apoptosis may be the common mechanisms for osteoporosis and AVN [25].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been many reports on risk factors for AVN development in SLE patients 19,20 . Although the results of studies are different, the use of corticosteroid, cumulative corticosteroid dose, immunosuppressive agents, neuropsychiatric involvement, antiphospholipid antibodies have been associated with AVN development in SLE patients 19,20 . However, there are few reports on the frequency and risk factors for AVN development in jSLE patients.…”
Section: Discussionmentioning
confidence: 99%